Susceptibility to prosocial and antisocial influence in adolescence following mindfulness training - Leung, JT; Piera Pi-Sunyer, B; Ahmed, SP; Foulkes, L; Griffin, C; Sakhardande, A; Bennett, M; Dunning, DL; Griffiths, K; Parker, J; Kuyken, W; Williams, JMG; et al. (Wiley, 2022)
Mindfulness training programmes have shown to encourage prosocial behaviours and reduce antisocial tendencies in adolescents. However, less is known about whether training affects susceptibility to prosocial and antisocial influence. The current study investigated the effect of mindfulness training (compared with an active control) on self-reported prosocial and antisocial tendencies and susceptibility to prosocial and antisocial influence. 465 adolescents aged 11–16 years were randomly allocated to one of two training programmes. Pre- and post-training, participants completed a social influence task. Self-reported likelihood of engaging in prosocial and antisocial behaviours did not change post-training, and regardless of training group, participants showed a higher propensity for prosocial influence than for antisocial influence. Finally, participants were less influenced by antisocial ratings following both training programmes.